2017
DOI: 10.1371/journal.pone.0175000
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of neurofibromatosis type 1 in a multi-morbid Inca child mummy: A paleoradiological investigation using computed tomography

Abstract: ObjectiveIn this study, an Inca bundle was examined using computed tomography (CT). The primary aim was to determine the preservation status of bony and soft tissues, the sex, the age at the time of death, possible indicators for disease or even the cause of death, as well as the kind of mummification. A secondary aim was to obtain a brief overview of the wrapping in order to gain additional information on the cultural background.Materials and methodsThe bundle belongs to the Museum of Cultures in Basel, Switz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Mummification techniques were also assessed (Davey et al, 2013, 2011; Martina et al, 2018; Wisseman & Hunt, 2014). Pathologies and anomalies identified in these examinations included: meningocele (Boano et al, 2009), cerebral hemorrhage (Papageorgopoulou et al, 2010), pectus excavatum, hepatomegaly, Harris lines (Zesch et al, 2016), probable neurofibromatosis 1, lung infection suggestive of tuberculosis (Panzer et al, 2017), “pressure erosion and distortion of the upper thoracic spine” suggestive of a neuroenteric duplication cyst (Loynes et al, 2018), indeterminate occipital fracture (Wisseman & Hunt, 2014), and probable tuberculous vertebral lesions (Öhrström et al, 2018).…”
Section: Literature Review: Resultsmentioning
confidence: 99%
“…Mummification techniques were also assessed (Davey et al, 2013, 2011; Martina et al, 2018; Wisseman & Hunt, 2014). Pathologies and anomalies identified in these examinations included: meningocele (Boano et al, 2009), cerebral hemorrhage (Papageorgopoulou et al, 2010), pectus excavatum, hepatomegaly, Harris lines (Zesch et al, 2016), probable neurofibromatosis 1, lung infection suggestive of tuberculosis (Panzer et al, 2017), “pressure erosion and distortion of the upper thoracic spine” suggestive of a neuroenteric duplication cyst (Loynes et al, 2018), indeterminate occipital fracture (Wisseman & Hunt, 2014), and probable tuberculous vertebral lesions (Öhrström et al, 2018).…”
Section: Literature Review: Resultsmentioning
confidence: 99%
“…Previous attempts at rediagnosing NF2 (or schwannomatosis) phenotypes on the basis of clinical and pathological reviews of old portraits and specimens' reports have been made. 3 On the basis of the above considerations, the full facial reconstruction of the Cro-Magnon male individual 1 should not include the additional smaller facial tumours (ie, the cutaneous neurofibromas), which belong to the NF1 phenotype. Previous CT scan reconstructions have shown NF1 phenotypes on the basis of stronger paleoradiological evidence.…”
Section: Did Cro-magnon 1 Have Neurofibromatosis Type 2?mentioning
confidence: 99%
“…What is unique about vitamin A deficiency is that food solutions exist and are feasible, even in low-income populations. Some 20 years ago, Noel W Solomons 3 concluded that red (unrefined) palm oil, the highest and most bioavailable plant source of provitamin A, did as well as vitamin A supplements. Red palm oil could do the work in most of sub-Saharan Africa, provided that it is not bleached during cooking and an efficient commercial distribution network is established.…”
mentioning
confidence: 99%
“…My lawsuit settlement against the National Institutes of Health did not give the WI-38 title to anyone. [2][3][4] The Bayh-Dole act specifically allows compensation for scientists who make discoveries using federal funds (I never received com pensation for my discoveries). However, billions of dollars were-and still are-made by the world's human virus vaccine manufacturers who continue using the WI-38 cell strain…”
Section: Subject Of the Vaccine Race Offers Perspective On Errorsmentioning
confidence: 99%
“…Second, the case cited by Ruggieri and colleagues is that of an Inca mummy of a child from the 17th century, with perfectly preserved organic tissues, allowing a diagnosis of multiple neurofibromas present in soft tissues; 3 it cannot reasonably serve as a comparison case with the dry skull of a fossil man.…”
Section: Authors' Replymentioning
confidence: 99%